Meningkatkan Akses dan Kualitas Pelayanan Kesehatan melalui Puskesmas Keliling: Pengalaman di UPT Puskesmas Tembuku I dalam Mengatasi Stunting dan Penyakit Lingkungan - Widyasari, Ida Ayu Putri Genta; Wedhaswari, Ida Ayu Made Idyani (IAHN Gde Pudja Mataram, 2024)
The Mobile Community Health Center program has been introduced as a strategy to increase access to health services in isolated areas. The main focus of this program is reducing stunting rates and controlling environmental-based diseases such as Acute Respiratory Infections and Dengue Hemorrhagic Fever. In its implementation, the Mobile Health Center succeeded in increasing community access to health services, with more than 50% of the village communities served experiencing an increase in health checks. Medical interventions and nutritional education have also contributed to reducing stunting rates, although the challenges in changing community behavior are still significant. Counseling on Clean and Healthy Living Behavior in schools and improving household sanitation also show positive impacts, although there are still obstacles in implementing healthy habits in the community. Fogging and abatement programs to control Dengue Hemorrhagic Fever as well as education regarding environmental sanitation management have shown positive results but need to be continued with a more intensive community-based approach. Despite progress, the biggest challenge remains behavior change which requires ongoing support and active community involvement. This evaluation shows that the Mobile Health Center is an effective health service model for improving access and quality of health in remote areas, although it needs strengthening in the areas of coordination between sectors and development of information technology to expand service coverage.